Bacteriological Etiology and Antibiotics Susceptibility Pattern in Blood Samples from the Patients Attending Emergency Department of a Tertiary Care Hospital, Nepal - Thapa, Rasmi; Chhetri, Dinesh; Batajoo, Kabita Hada; Shrestha, Ashis; Acharya, Samita; Shrestha, Roshana; Karna, Roshan; Upadhya, Amrita (Journal of Karnali Academy of Health Sciences, 2021)
Background: Blood cultures are among the most important laboratory tests performed in the diagnosis of infections. Blood-stream infections cause significant morbidity and mortality, increase in length of hospital stay and increased cost of care. Undiagnosed blood-stream infections and frequent inappropriate antibiotic use contributes to emergence of drugresistant bacteria pathogens. Objectives: This study was carried out to identify likely bacteriological etiology and its antibiotics susceptibility profile in blood stream infection from the patients attending Emergency Department of a Tertiary Care Hospital, Nepal. Methodology: This study was conducted between July and August of 2017. A total of 282 blood specimens were collected from the patient attending Emergency Department of a tertiary care hospital and reported with signs and symptoms of fever, body ache, relative bradycardia and burning micturition. Collected Blood specimen was kept in a container containing 50ml of Tryptone Soy-Broth and sent to the microbiology lab for culture and antibiotic susceptibility test (AST). All procedure, specimen collection, culture and AST were performed from isolates by using standard protocol. Data were entered and analyzed by using SPSS. Results: Among the total (282), male patients were more (58.2%) and more patients were from 41-50 years age group. Only 18 patients were from age of above 60 years. Out of the total specimens (282), no growths were reported in 74.11% (209) and growth of microorganism was reported in 10.28% (29) blood specimens. The most common bacterial isolates were found Enterobacter species reported highest percentages (48.27%), followed by Streptococcus pneumoniae (13.79%) and Salmonella typhi (10.34%) Enterobacter species was more sensitive to Chloramphenicol, Amikacin and Gentamycin. While Streptococcus pneumoniae was sensitive to most of the antibiotics, it was found that 65.3% bacterial isolates were resistant to Cephalosporin. Conclusion: Contaminated blood samples were found more, therefore, emphasis should be given in reducing the contamination. Proper cleaning of skin with antiseptic and guidelines to draw blood for culture should be familiarized and strictly followed while drawing the blood and others from Emergency Department.